TINJAUAN FIQIH JINAYAT TERHADAP PELAKU ZINA MENURUT KITAB UNDANG-UNDANG SIMBUR CAHAYA - Setiawan, Muhamad (Universitas Islam Negeri Raden Fatah Palembang, 2020)
In formal and material law, Simbur Cahaya as a law regulates the sanctions and the application of sanctions to adultery offenders in the context of customary criminal law. Inseparable from the customary criminal law in Simbur Cahaya, formal law and material law can be studied and analyzed and analyzed from the perspective of Islamic criminal law / Fiqh Jinayah law. The problems raised in the focus of this study are: (1). How are the sanctions for adultery perpetrators by Pasirah (as an implementation of the Simbur Cahaya Book)? (2). How is the Fiqh Jinayat Review of Adultery Perpetrators According to the Simbur Light Book? This research was conducted using normative juridical legal research methods or literature analysis, the type of data used is qualitative data. The data source used in this study is secondary data obtained from literature studies, which are then processed and analyzed by content analysis in order to obtain a conclusion. Based on the research results that legally the customary sanctions in the criminal act of adultery in Simbur Cahaya are in the form of a certain amount of fines in addition to the sanctions on marriage and sanctions for mbasuh hamlet. While the application of the formal law appears to be closer to the current form of justice, it is just that there are some differences in the customary court process. As seen from the Fiqih Jinayat, the material law is not in accordance with the Fiqih Jinayat textually, but in the perspective of maqashid al-syari'ah the punishment of fines, marriage, and village cleaning on adultery in the Simbur of Light is contextually not contradicting with Fiqih Jinayat and is classified as a finger. ta'zir is a type of ta'zir garamah (ta'zir fine). Whereas the review of Fiqih Jinayat in formal law or the customary justice system in Simbur Cahaya is not against Islamic law although it is slightly different in the process from the jinayat court at the time of Rasulullah SAW because in Islamic criminal law there is not too much emphasis on the standard form of formal law or the jinayat judicial system. itself. Keywords: Maqashid Al-Syari’ah, Customary sanctions, Simbur Cahaya, Adultery